Organ Dysfunction in Patients with Advanced Melanoma Treated with Immune Checkpoint Inhibitors. (3rd October 2020) - Spillane, Susan; Baxi, Shrujal; Torres, Aracelis Z.; Lenis, David; Freedman, Andrew N.; Mariotto, Angela B.; Sharon, Elad
Abstract: Background: Real‐world data enables evaluation of immune checkpoint inhibitor (ICI) use in advanced melanoma management. We examined characteristics and outcomes of ICI‐treated patients with advanced melanoma and organ dysfunction (baseline and emergent). Materials and Methods: This retrospective observational study used electronic health records derived from a nationwide data set to examine advanced melanoma patients treated with first‐line ICIs (2011–2018). Clinical characteristics, real‐world time to treatment discontinuation (rwTTD), and overall survival (OS) were analyzed for patients with normal organ function and those with organ dysfunction prior to ICI initiation. Patients with emergent dysfunction in the 90 days following ICI initiation were identified, and potentially associated characteristics were explored. Results: Of 2, 407 patients included, 1, 884 and 1, 717 had evaluable renal and hepatic laboratory values, respectively. Patients with baseline renal dysfunction (2.4%) were older and more frequently male, and less frequently treated with ICI combinations, than patients with normal renal function. Patients with baseline hepatic dysfunction (2.8%) were similar to patients with normal hepatic function regarding demographics and treatments received. Patients with baseline organ dysfunction displayed shorter rwTTD and OS. Among patients with normal baseline organ function, 4.6% and 7.4% developed renal and hepatic dysfunction within 90 days of ICI initiation, respectively; this was associated with combination ICI treatment. Conclusion: Patients with advanced melanoma and baseline organ dysfunction frequently receive ICI treatment but have poorer clinical outcomes than patients with normal organ function. Among patients with normal renal and hepatic function at ICI initiation, emergent organ dysfunction rates in this real‐world cohort are similar to those reported in clinical trials. Implications for Practice: Real‐world data provide an opportunity to understand treatment patterns, toxicity, and clinical outcomes among patients treated outside of clinical trials. This study confirms that patients with advanced melanoma and baseline renal or hepatic dysfunction are being treated with ICI therapy more frequently as monotherapy than in combination therapy. For those real‐world patients with normal baseline organ function, emergent renal and hepatic dysfunction are both more common in patients treated with combination versus ICI monotherapy. Abstract : Evidence shows improved survival for patients with advanced melanoma treated with the CTLA‐4 inhibitor, ipilimumab, and PD‐1 inhibitors. This article examines characteristics and outcomes of patients with advanced melanoma and organ dysfunction treated with immune checkpoint inhibitors, for patients with both baseline dysfunction and treatment‐emergent toxicity, using a dataset of real world patients.